A Shakespearean Exploration of Erasmus' festine lente. (3rd July 2019) - Drouet, Pascale
ABSTRACT: Shakespeare may have been influenced by Erasmus' work, by both his Moriae Encomium ( The Praise of Folly ) and his Adagia. Among more than three thousand adages, one seems particularly relevant as regards time and the way to deal with and experience it in Shakespeare's drama, his adage 1001: " Festina lente : make haste slowly, " which became one of the most famous Renaissance maxims expressed by a variety of emblems such as a dolphin around an anchor, a tortoise carrying a sail, a butterfly on a crab. After considering the origin and transmission of the paradoxical proverb (Octavius Augustus, Titus Vespasianus and Aldus Manutius) and Erasmus' various interpretations of this demanding ability to "rightly combine promptness at the opportune moment with cautious deliberation, " this paper argues that tragic as well as ironically comic events in Shakespeare's plays are triggered from the characters' inability to follow the Erasmian adage, both as regards private and political issues, out of whether rashness, over-hastiness and lack of mental control or excess of deliberation and untimely delaying.